'Re-coding' environmental regulation – a new simplified metric for daylighting verification during the window and indoor space design process. (4th July 2022) - Nigra, Marianna; Lo Verso, Valerio R. M.; Robiglio, Matteo; Pellegrino, Anna; Martina, Maddalena
ABSTRACT: The role of regulation in fostering or hindering sustainable development has been largely discussed. Yet, empirical studies on how to act in reviewing and modifying normative structures seem to be lacking within the academic debate. This work presents the experience undertaken by the research center F UL L at the Politecnico di Torino (Turin, Italy), in supporting the local Municipality to simplify, disambiguate and redefine the current environment/energy regulation system. The paper particularly focuses on the methodological approach utilized to review rules in relation to daylighting in the local Energy Annex Code. This document contained mandatory and voluntary requirements and includes daylighting among the voluntary ones, through the average Daylight Factor DFm . It also addressed the window design through the RAI (Ratio Aerial Illuminating, defined as window area to room area ratio). The Municipality reports that building practitioners underuse the daylighting practice based on DFm, rather relying on RAI, because of its simplicity. Consequently, the Municipality gave mandate to F UL L to define a new daylight indicator, to be included among mandatory requirement and meant to be more accurate than RAI but simple enough to promote its application. For this purpose, the 'RAI-enhanced' indicator was defined, as a function of: ( i ) glazing area Sg ; ( ii ) glazing visible transmittance Tv, ( iii ) floor area S floor ; ( iv ) obstruction angle α, considering buildings ahead of window, overhangs, and loggias. Based on the results, the paper explains how the daylighting part of the energy regulation system was informed and reviewed in the case of the Municipality of Turin.